A study on needs to design English teaching materials at vocational school - Lailatul Abidah; Mifta Libby Askangela; Declarieta Berlianty; Noor Aina Herliana; Nunuk Nur Qomariyah; Ryan Permadi Teladan; Fardini Sabilah (UPT Bahasa Universitas Tanjungpura, 2023)
English for Specific Purpose (ESP) instruction in vocational schools necessitates the use of English materials that are tailored to the students' particular requirements. However, the English materials currently available for vocational institutions lack an adequate needs analysis. In order to address this issue, the purpose of this study is to determine the requirements of students in the computer and network engineering department for procedure text teaching materials. Eleventh-grade students majoring in computer and network engineering were selected by simple random sampling and surveyed for the study. The results indicated that the primary objective of the students' explanation-based learning process was to enhance their speaking skills. In addition, instructors favoured interactive, engaging, and simple-to-understand multimedia learning to teach English. This research can be used as a guide for designing English language instructional materials that meet the requirements of vocational students, especially those majoring in computer and network engineering.